Evidence of cationic Pt active for water-gas shift reaction: Pt-doped BaCeO3 perovskite - Rajesh, Thattarathody; Rajarajan, Anakot K.; Gopinath, Chinnakonda S.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Precious metal incorporated into stable lattices like perovskites can be envisaged as an alternative catalysts to address deactivation problems. Here we report the barium cerate perovskite doped with varying amounts of Pt as catalysts for the water-gas shift reaction whereby ionic Pt is evidenced to be active. It is found that maximum CO conversion occurs above 325 degrees C and increases more than 2-fold after the first cycle. XPS analysis shows that after the first cycle, more ionic Pt species are present on the surface of the catalyst. X-ray and neutron diffraction studies also indicate the presence of oxygen vacancies that increases with increasing Pt substitution.

Confined space synthesis of fully alloyed and sinter-resistant AuPd nanoparticles encapsulated in porous silica - Samanta, Anupam; Rajesh, Thattarathody; Devi, R. Nandini (Journal of Materials Chemistry A, 2014)
Facile synthesis of highly sinter-resistant silica encapsulated Au-Pd alloy nanocatalysts with average particle size stabilized at similar to 4.5 nm even after calcination at 750 degrees C temperature is reported. The synthesis was achieved by utilizing thiol protected ultra small clusters of Au and Pd as precursors for silica encapsulation. The presence of intimate mixtures of the clusters within silica encapsulation ensures the formation of fully alloyed nanoparticles at high temperatures, at the same time controlling further growth and sintering. At optimum alloy compositions, these catalysts showed high catalytic activity for CO oxidation displaying low light-off temperatures.

Effect of pt incorporation in LaBO3 (B = Mn, Fe, Co) perovskites on water gas shift activity - Rajesh, Thattarathody; Upadhyay, Anuj; Sinha, Anil K.; Deb, Sudip K.; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt incorporated perovskites LaBO3 (B = Mn, Co, Fe) were synthesised and characterised to understand the charge state of Pt in these materials. At the temperature range used in this study, Pt could be stabilised in ionic form in Co and Fe perovskites but not in LaMnO3. Consequent to incorporation of Pt in +2 and +4 oxidation states, reduction in B site ion charge state occurred, enhancing oxygen vacancies. Pt doped Co and Fe perovskites showed high activity for CO conversion under water gas shift conditions but the activity characteristics were found to be different for the two catalysts; LaCo1-xPtxO3-delta showed methanation whereas the Fe counterpart was active in water gas shift reaction. It was also observed that methanation could be decreased and water gas shift enhanced in case of Pt doped Co perovskite when compared to Pt impregnated perovskite or mixed oxides. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Methanation; Perovskites; Pt doping; Water gas shift reaction; XANES

Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS

Resistance to ionic pt insertion in oxygen excess LaMnO3 perovskite lattices and its effect in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt doped and impregnated LaMnO3 perovskites are synthesized at different temperatures and Pt and Mn states are compared in an attempt to get insight into extent of lattice incorporation of Pt in perovskite. Various characterization studies indicate that oxygen excess system like LaMnO3 presents substantial resistance to B site doping with Pt. This behavior is different from other oxygen deficient perovskites like LaCoO3 and LaFeO3 in which lattice incorporation stabilizes the active species against sintering. Water gas shift reaction was used as a probe reaction to understand the effect of this difference in the activity. In case of LaMnO3, failure in lattice substitution leads to sintering and deactivation at high synthesis temperatures (>= 700 degrees C) in both impregnated and doped samples. In doped samples, however, a strong interaction of Pt species with a persistent amorphous phase prevents sintering at lower synthesis temperature thereby enhancing the activity when compared to impregnated sample. The study reveals a possible mechanism in which only Pt(0) species is active with perovskite playing a minimal role in this system due to the resistance to lattice incorporation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxygen excess; Perovskites; Water gas shift reaction; XPS; XRD

Role of oxygen vacancies in water gas shift reaction: activity study on BaCe0.98-xYxPt0.02O3-delta perovskites - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Physical Chemistry C, 2014)
Oxygen vacancies are suggested to play an important role in reactions like water gas shift where the redox mechanism is crucial. Pt-doped BaCeO3 perovskite, moderately active for water gas shift reaction, is selected for further understanding the role of oxygen vacancies, since perovskite lattice can tolerate and stabilize vacancies facilitating an accurate quantification. Vacancies are created in the system by systematic doping of increasing amounts of Y. Structure and activity studies reveal that the 6% Y-substituted compound which has the most symmetric B site coordination environment exhibits the highest activity. Hence, it is not the extent of vacancies but their structural characteristics which are found to be decisive. Symmetric coordination around B ions facilitates water adsorption and dissociation by lowering the energy barriers due to the creation of an isotropic environment.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2017)
The extent of alloying and the alloy composition, which are crucial in determining the activity and selectivity of bimetallic catalysts, were studied in porous silica encapsulated AgPd catalysts using XRD, HRTEM and HAADF-STEM. Water-dispersible ligand protected Pd ultra-small clusters and Ag nanoparticles of three different sizes were used as the precursors. The high reactivity of Pd ultra-small clusters enhanced the alloying of larger Ag nanoparticles to some extent. Encapsulation appeared to have minimised the sintering of the resultant nanoparticles. The earlier suggestions of the role of d-band positions with respect to adsorption energies holds good for the AgPd system and alloying enhances the activity. Alloy with the composition of Ag50Pd50 was found to be the most active with the reaction rate enhanced two fold compared to that in other compositions. Other factors like particle size and sinter-resistance also played important roles in enhancing the activity of these catalysts.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties (vol 41, pg 14652, 2017) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2020)